Plasma adiponectin is a more specific marker of fatty liver than a marker of metabolic syndrome in Japanese men. (January 2014) - Yatsuzuka, Shin-ichi; Shimomura, Younosuke; Akuzawa, Masako; Ando, Yoshitaka; Kobayashi, Isao; Nakano, Takamitsu; Tokita, Yoshiharu; Nagamine, Takeaki; Ono, Hiromi; Tanaka, Akira; Schaefer, Ernst; Nakajima, Katsuyuki
Background: The association of plasma cardiovascular risk markers and metabolic syndrome (MetS) with non-alcoholic fatty liver disease (NAFLD) has not been well defined. Methods: Japanese men ( n  = 809) had standard anthropometric measurements done, and had their liver fat quantitated by ultrasound. Three groups were identified: (1) normal controls without significant disease, (2) preliminary-metabolic syndrome (pre-MetS) cases and (3) MetS cases. Plasma adiponectin, high sensitivity-C reactive protein (hs-CRP), HOMA-IR, lipids, lipoproteins and liver enzymes were evaluated among the three groups. Results: The prevalence of fatty liver was 13% in controls, 39% in pre-MetS and 62% in MetS. Plasma adiponectin and high density lipoprotein cholesterol (HDL-C) were significantly decreased, and HOMA-IR, hs-CRP, TG, remnant lipoproteins (RLPs) and small dense-LDL-C (sd LDL-C) were significantly increased in subjects with fatty liver compared to those without fatty liver. Multivariate analyses of serum parameters associated with fatty liver revealed that adiponectin and hs-CRP were more strongly associated with the presence of fatty liver than waist circumference. However, HOMA-IR, HDL-C, TG, RLP-C, RLP-TG and sd LDL-C were more strongly associated with waist circumference than with fatty liver. Factor analysis revealed that adiponectin and HDL-C were linked to liver enzymes, lipoproteins and HOMA-IR associated with fatty liver, but not with waist circumference. Conclusions: Adiponectin was found to be a more specific diagnostic marker for the presence of fatty liver regardless of MetS status, and was inversely correlated with liver enzyme concentrations. However, RLPs were found to be more specifically associated with the presence of MetS.